A new species of Phonotimpus Gertsch & Davis, 1940 (Araneae: Phrurolithidae) from Mexico - Chamé-Vázquez, David; Ibarra-Núñez, Guillermo (Zootaxa, 2019)
The genus Phonotimpus Gertsch & Davis, 1940 includes four species all known only from Mexico (World Spider Catalog 2018). P. separatus and P. eutypus were described by Gertsch & Davis (1940) from San Luis Potosí and from Nuevo León, respectively. Phonotimpus pennimani and P. talquian, described by Chamé-Vázquez, Ibarra-Núñez & Jiménez (2018), are the southernmost species in this genus (Chamé-Vázquez et al. 2018), and have restricted allopatric geographic distributions in Chiapas. This genus differs from other American phrurolithid genera by the following combination of characters: posterior eye row recurved, posterior median eyes closer to posterior lateral eyes than to each other, posterior median eyes smaller than posterior lateral eyes, females with dorsal scutum on the opisthosoma; palpi of males with retrolateral and dorsal tibial apophyses not joined at the base, and copulatory bulb with a conductor, embolus and embolar basal process (Gertsch & Davis 1940; Penniman 1985; Chamé-Vázquez et al. 2018). In this paper, a new species of Phonotimpus is described and illustrated, based on specimens collected in soil of a pine-oak forest in the state of Mexico.